Higher-Education Administrators: When the Future Does Not Make a Difference - Logue, A.W.; Anderson, Yenny D. (Psychological Science, 2001)
The relationships between administrative actions and their long-term consequences were investigated in 14 people beginning training to become high-level college and university administrators, 19 people who had just finished that training, and 44 provosts (chief academic officers) at colleges and universities in the northeastern United States. The experienced administrators (those who had completed the training plus the provosts) were significantly more likely than the trainees to mention long-term consequences when describing their past and possible future administrative actions. However, in hypothetical choice situations, the experienced administrators were also significantly more likely than the trainees to choose smaller amounts of funds available immediately for their units versus larger amounts of promised future funds. With experience, administrators may both become more aware of their actions' long-term consequences and learn that they are unlikely to receive promised future funds. The contingencies in effect for higher-education administrators may lead them to make choices that do not result in their institutions meeting the highest standards.